The interplay between nonalcoholic fatty liver disease and atherosclerotic cardiovascular disease - Finney, Alexandra C.; Das, Sandeep; Kumar, Dhananjay; McKinney, M. Peyton; Cai, Bishuang; Yurdagul, Arif; Rom, Oren (Frontiers in Cardiovascular Medicine, 2023)
Therapeutic approaches that lower circulating low-density lipoprotein (LDL)-cholesterol significantly reduced the burden of cardiovascular disease over the last decades. However, the persistent rise in the obesity epidemic is beginning to reverse this decline. Alongside obesity, the incidence of nonalcoholic fatty liver disease (NAFLD) has substantially increased in the last three decades. Currently, approximately one third of world population is affected by NAFLD. Notably, the presence of NAFLD and particularly its more severe form, nonalcoholic steatohepatitis (NASH), serves as an independent risk factor for atherosclerotic cardiovascular disease (ASCVD), thus, raising interest in the relationship between these two diseases. Importantly, ASCVD is the major cause of death in patients with NASH independent of traditional risk factors. Nevertheless, the pathophysiology linking NAFLD/NASH with ASCVD remains poorly understood. While dyslipidemia is a common risk factor underlying both diseases, therapies that lower circulating LDL-cholesterol are largely ineffective against NASH. While there are no approved pharmacological therapies for NASH, some of the most advanced drug candidates exacerbate atherogenic dyslipidemia, raising concerns regarding their adverse cardiovascular consequences. In this review, we address current gaps in our understanding of the mechanisms linking NAFLD/NASH and ASCVD, explore strategies to simultaneously model these diseases, evaluate emerging biomarkers that may be useful to diagnose the presence of both diseases, and discuss investigational approaches and ongoing clinical trials that potentially target both diseases.